The Crime Of Sexual Exploitation Of Minor Girls: A Study From The Perspective Of Islamic Jurisprudence And Its Impact On Human Health - El-Sayed Abu El-Ala, Khaled Fouad (Journal of Neonatal Surgery, 2025)
The research aimed to define the crime of sexual exploitation of minor girls, and its ruling from the perspective of Islamic jurisprudence, and to monitor the effects thereof, and the penalty for sexual exploitation of minor girls, and to clarify its effects from both the Sharia and legal perspectives. The study relied on the descriptive method, and within that framework adopted the analytical approach. It resulted in many findings, the most prominent of which are as follows: Sexual exploitation is any sexual contact between a child and an adult for the purpose of satisfying the sexual desires of the latter, using his influence to dominate the child. Forms of sexual exploitation include: providing money, shelter, food, goods, or services to a vulnerable person in exchange for sexual relations or sexual services — this constitutes sexual exploitation. A minor girl is defined as one who has not yet reached the age of majority, i.e., the age of 18 years — this is the view of positive law. Islamic Sharia does not distinguish between sexual exploitation of the minor or the adult; as it considers sexual exploitation a form of coercion into fornication. The penalty for sexual exploitation in Islamic Sharia falls under the punishment of ḥadd al-ḥirābah, as it constitutes spreading corruption upon the earth and the propagation of indecencies. The penalty for sexual exploitation under Saudi law is imprisonment for a term not exceeding two (2) years, and a fine not exceeding one hundred thousand Saudi riyals (SAR 100,000), or either of the two penalties. The crime of sexual exploitation of minor girls is extinguished by death. The spread of the crime of sexual exploitation of minor girls affects human health; as it leads to the spread of physical and psychological diseases requiring substantial expenditure for treatment and eradication. The researchers recommend the following: Calling upon governments to tighten penalties related to sexual exploitation. Increasing educational awareness regarding the prohibition of this crime and clarifying its penalties.